2021
DOI: 10.1210/clinem/dgab303
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of PGRMC1 During Human Decidualization Using an In Vitro Approach

Abstract: Context Non-classical membrane progesterone receptor (mPRs) and PGRMC1 expression have been detected in endometrium, but their role in decidualization was not yet investigated. We previously demonstrated PGRMC1 downregulation in receptive endometrium and that its overexpression inhibits decidualization. Furthermore, during decidualization, PGRMC1 mainly interacts with proteins involved in biosynthesis, intracellular transport and mitochondrial activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…In both tested cells lines-T-HESC cells from fibroblastic origin and HEC-1A from epithelial origin-the most striking effect of AG-205 highlighted by our transcriptomic analyses was increased mRNA concentration of several enzymes involved in cholesterol biosynthesis, the sterol-sensitive regulator INSIG1 and specific enzymes involved in steroidogenesis. Our results are in global agreement with the reported effects of AG-205 in the culture of primary stromal cells induced to decidualize in response to combined estradiol and progesterone [14]. However, these effects were produced in the absence of progesterone, suggesting that they are not relevant to decidualization, and, most importantly, they were not mimicked by siRNA-mediated down-regulation of PGRMC1 or any other related MAPR (PGRMC2, NENF or CYB5D2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In both tested cells lines-T-HESC cells from fibroblastic origin and HEC-1A from epithelial origin-the most striking effect of AG-205 highlighted by our transcriptomic analyses was increased mRNA concentration of several enzymes involved in cholesterol biosynthesis, the sterol-sensitive regulator INSIG1 and specific enzymes involved in steroidogenesis. Our results are in global agreement with the reported effects of AG-205 in the culture of primary stromal cells induced to decidualize in response to combined estradiol and progesterone [14]. However, these effects were produced in the absence of progesterone, suggesting that they are not relevant to decidualization, and, most importantly, they were not mimicked by siRNA-mediated down-regulation of PGRMC1 or any other related MAPR (PGRMC2, NENF or CYB5D2).…”
Section: Discussionsupporting
confidence: 92%
“…In the human endometrium, progesterone is a critical inducer of modifications occurring to favour blastocyst implantation and pregnancy, including decidualization, i.e., a specific differentiation of the endometrial stromal cells. PGRMC1 is expressed in the human endometrium and its potential contribution to decidualization was recently reported [14]. Interestingly, the addition of AG-205 to endometrial stromal cells undergoing artificial decidualization in response to progesterone (combined with estradiol) upregulated expression of genes related to metabolism, molecular transport and hormonal biosynthesis.…”
Section: Introductionmentioning
confidence: 93%
“…We and others previously demonstrated that endometrial PGRMC1 expression decreases during the secretory phase of the menstrual cycle and the small interfering RNA (siRNA)-mediated knockdown and inhibition of PGRMC1 promotes ESC decidualization in vitro [ 26 , 27 ]. However, the relationship between the PGRMC1 expression and cellular senescence in ESCs during decidualization has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that progesterone stimulates the endometrium to directly synthesize prolactin [ 48 , 49 ]. We detected the upregulation of prolactin secretion in adenomyosis in the same pattern as in the normal endometrium, mediated by both cAMP and progesterone.…”
Section: Discussionmentioning
confidence: 99%